Are learners ready for Englishes in the EFL classroom? A large-scale survey of learners' views of non-standard accents and teachers' accents. (November 2020) - Tsang, Art
Abstract: The adherence to Received Pronunciation (RP) and General American (GA) as standard models in English-as-a-foreign-language (EFL) education has been challenged in recent decades. Scholars have advocated (1) using a wider variety of accents as input for EFL listening and (2) intelligibility over nativelikeness in EFL pronunciation. However, learners' views of these advocacies and their views of whether EFL teachers need or need not speak with RP/GA have remained under-researched. This large-scale survey explored Hong Kong secondary-level learners' views (n = 1300) of non-standard accents in EFL education and EFL teachers' accents. Participants' self-rated English proficiency and prior exposure to different accents were also included in the analyses. The results show that, surprisingly, the participants were only slightly favourable towards teachers with RP/GA and they were slightly against the notion that those without RP/GA are inappropriate EFL teachers. With regard to incorporating non-RP/GA accents in EFL listening, they were neutral towards including other L1 accents and slightly negative towards L2 accents. Differences in views were found when the participants were categorized into groups of different proficiency and prior exposure. This article ends with a discussion of these findings and their implications.